2-Phase dynamic simulation of deep sand compaction to reduce liquefaction. (2017) - Nagula, Sparsha; Grabe, Juergen
Abstract: A numerical model of a shallow foundation resting on sand is set up to simulate the liquefaction of partially saturated sand subjected to a confined transient loading. The foundation is observed to undergo large settlements due to liquefaction of sand. In order to analyze the feasibility of deep vibration compaction in liquefaction mitigation, saturated sand was subjected to compaction and later the same compacted sand with foundation was subjected to a confined transient loading. It was observed that the compaction technique reduced liquefaction drastically, suggesting that deep vibration compaction can be effectively used as a liquefaction mitigation measure.The compaction method includes densification of loose sands by means of shear deformation processes imparted by horizontal vibrations of vibrator probe at the required soil depth. A coupled hypoplastic constitutive model is used to characterize the stress-strain behavior of the saturated sand.